The Concept of Ugliness in Buddhism - ปั้นเหน่งเพชร ผศ.เยื้อง (วารสารพุทธศาสตร์ศึกษา, 2018)
This article attempts to investigate the concept of ugliness in Buddhism and to explore the doctrinal reflection on ugliness. The results revealed that ugliness is the displeasing in appearance, which has a synonym as a mischief or Apakārā, foulness or Asubha. The nature of ugliness can be classified into 4 type viz. 1) Gati-vipatti: failure as regards place of birth, 2) Upadhi-vipatti: failure as regards the deformed or unfortunate body, 3) Kàla-vipatti: failure as regards unfortunate time and 4) Payoga-vipatti: failure as regards undertaking. In addition, the ugliness is also referred to the failure in conduct as appeared in the Disciplines or Vinaya. As regards the type of ugliness that is called Vipatti: failure, it can be divided into 4 categories viz. 1) Sãla-vipatti: falling away from moral habit, 2) âcàra-vipatti: falling away from good behavior, 3) Diññhi-vipatti: falling away from right view and 4) âjãva-vipatti: falling away from right mode of livelihood. However, the purposes of ugliness as found in the Buddhist doctrine are to eliminate all sensual pleasures and to stimulate the moral reflection. The moral reflections take place after perceiving the ugliness from the sculpture or painting that reflects the fruition of unwholesome actions. For the sake of better understanding the real nature of ugliness, it can be reflected by five means as 1) reflection on the Five Aggregates, 2) reflection on measuring (or judged) by one’s reputation, 3) reflection on the thirty two parts of body and 4) reflection on the Asubha meditation and 5) reflection on the higher training in proper conduct.